2016
DOI: 10.18251/ijme.v18i2.1147
|View full text |Cite
|
Sign up to set email alerts
|

The Needs of Educators in Intercultural and Bilingual Preschools in Chile: A Case Study

Abstract: Several studies have examined the lack of or the insufficient preparation of K-12 educators to work in intercultural and bilingual (IBE) schools in Chile, but little is known about the preparation of educators to teach in IBE preschools. Even less is known about teachers' perceptions of their own preparation. This work contributes to a growing body of literature that examines the experiences and practice of second language teachers in Indigenous language education settings from a sociocultural perspective. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…She identified that these three have different views on interculturality, in which Peruvian views IC as harmonious dialogue among cultures, Ecuadorian views it as a strengthened indigenous identity, and Bolivian viewed it as a strengthened national identity based on respect for all. A recent study in Chile by Becerra-Lubies and Fones (2016) suggests teachers in Chilean contexts need to equip themselves with IC components to successfully transfer and teach in bilingual programs. What is implied in this research is that IC is related to building harmony among different ethnic groups and maintaining local identities.…”
Section: Research Of Ic On Bilingualism and Bilingual Educationmentioning
confidence: 99%
“…She identified that these three have different views on interculturality, in which Peruvian views IC as harmonious dialogue among cultures, Ecuadorian views it as a strengthened indigenous identity, and Bolivian viewed it as a strengthened national identity based on respect for all. A recent study in Chile by Becerra-Lubies and Fones (2016) suggests teachers in Chilean contexts need to equip themselves with IC components to successfully transfer and teach in bilingual programs. What is implied in this research is that IC is related to building harmony among different ethnic groups and maintaining local identities.…”
Section: Research Of Ic On Bilingualism and Bilingual Educationmentioning
confidence: 99%
“…The absence of guidance for teaching in rural contexts in the Chilean Teachers' Professional Program evidences the lack of discussion about how to improve rural and Indigenous education through teachers' professional development. In 1978, the Intercultural Program was implemented, and this is still being taught in schools (Becerra-Lubies & Fones, 2016). This program gives some flexibility for rural schools with Indigenous students to adjust the National Curriculum according to the students' needs (Catriquir & Duran, 1997).…”
Section: The Chilean Contextmentioning
confidence: 99%
“…How could these skills be developed in teacher education programs? Most of the research that has been undertaken in Indigenous communities and schools in Chile is in the south of the country because these regions are where the majority of the Indigenous population are located (Becerra-Lubies & Fones, 2016;Ortiz, 2009). Thus, the reality of local Indigenous peoples' education, and the experiences of their teachers in the North of Chile, seems to be unknown.…”
Section: The Chilean Contextmentioning
confidence: 99%
See 2 more Smart Citations